2011
DOI: 10.1158/1078-0432.ccr-10-2307
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16 and Retinoblastoma Determines Response to CDK4/6 Inhibition in Ovarian Cancer

Abstract: Purpose PD-0332991 is a selective inhibitor of the CDK4/6 kinases with the ability to block retinoblastoma (Rb) phosphorylation in the low nanomolar range. Here we investigate the role of CDK4/6 inhibition in human ovarian cancer. Experimental Design We examined the effects of PD-0332991 on proliferation, cell-cycle, apoptosis, and Rb phosphorylation using a panel of 40 established human ovarian cancer cell lines. Molecular markers for response prediction, including p16 and Rb, were studied using gene expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
207
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(229 citation statements)
references
References 24 publications
(34 reference statements)
21
207
1
Order By: Relevance
“…S7). Similar results have been reported previously for cotreatment experiments with carboplatin and palbociclib (65). Of note, the dosing regimen is expected to have a critical role in avoiding potential antagonistic effects.…”
Section: Cdk4/6 Inhibitors As Adjunct Therapy During Cisplatin Treatmsupporting
confidence: 84%
“…S7). Similar results have been reported previously for cotreatment experiments with carboplatin and palbociclib (65). Of note, the dosing regimen is expected to have a critical role in avoiding potential antagonistic effects.…”
Section: Cdk4/6 Inhibitors As Adjunct Therapy During Cisplatin Treatmsupporting
confidence: 84%
“…In addition, this stratification could be used to determine novel second-line treatment options such as CDK4 inhibition (which inhibits the interaction with cyclin D1 resulting in hypophosphorylation of RB1 and E2F inactivation). 15 Konecny et al reported that ovarian cancer cell lines with RB1 deletions and CCNE1 gains are more resistant to CDK4 inhibitors, whereas those with CDKN2A gene deletions and decreased protein expression were more sensitive. 15 We found that CDKN2A and/or CDK4 gene deletions are rare in high-grade serous carcinoma and that cyclin D1 overexpression is predominant in the p16 hetero/ RB1 þ tumors.…”
Section: Discussionmentioning
confidence: 99%
“…15 Konecny et al reported that ovarian cancer cell lines with RB1 deletions and CCNE1 gains are more resistant to CDK4 inhibitors, whereas those with CDKN2A gene deletions and decreased protein expression were more sensitive. 15 We found that CDKN2A and/or CDK4 gene deletions are rare in high-grade serous carcinoma and that cyclin D1 overexpression is predominant in the p16 hetero/ RB1 þ tumors. Patients within the p16 hetero/ RB1 þ subgroup may be predicted to benefit most from CDK4 inhibitor treatments, in contrast to patients with cyclin E1 gains/amplifications in the p16 homo/RB1 þ subgroup and RB1 deletions in the p16 homo/RB1 À subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cellular effectiveness has also been reflected in various tumor xenograft models. [95][96][97][98][99][100][101][102] Currently, in its phase III clinical trial, PD0332991 is being tested in patients with squamous cell lung cancer and has been granted accelerated approval for use in combination with letrozole for the treatment of hormone receptor positive/human epidermal growth factor receptor 2 negative (HR C /HER2 ¡ ) breast cancer in postmenopausal women for their metastatic disease (http://www.fda.gov/). Despite the exciting therapeutic outcomes obtained from this combination therapy and its advantage in combating drug resistance, there should be a certain degree of caution when considering combination regimens.…”
Section: Structural Features and Regulationmentioning
confidence: 99%